Simulation Study of Elliptical Thin-Walled Structure Crash Box with Holed Initiator Through Axial Impact - Jeffey Jep Brown; Al Emran Ismail; Dave Kidau Anak Wilie Chiak Mong (Research Progress in Mechanical and Manufacturing Engineering, 2022)
Crash box is a thin-walled structure which is used as a medium for energy absorption to increase crashworthiness of vehicles during accidents by reducing impact or energy received by passengers in the passenger compartment of a vehicle. This study is to analyse the energy absorption performance of A36 steel elliptical shaped crash box with holed initiators. Using ANSYS simulation software, the effects of holes on elliptical shaped crash box by subjecting it to axial impact are analysed. Each designed elliptical crash box with holed initiator is analysed using performance indicators such as energy absorption value, crush force efficiency and specific energy absorption as to understand effects of holes on elliptical shaped crash box. it was found that energy absorption of the crash box is significantly increased but CFE values are also significantly decreased.